Improvement of methods and means of control of deviations from straightness by using acousto-optic heterodyne laser measuring systems - E. V. Leun (Омский научный вестник)
The article deals with the construction of high-precision acoustooptic (AO) heterodyne laser measurement systems for monitoring deviations from straightness when working in continuous mode with phase-digital Δφ(Δl y )–ΔNout and frequency-digital Δf(Δl y )–ΔNout transformations, as well as in pulse mode. It discusses the use of solid-state AO modulators, phase-locked loop systems phase and frequency together with the fiber phasemodulaters and precision ADC. The variants of linearization of the transformation function, increasing the resolution are proposed. It discusses the possibility of implementing laser measurement systems with support channels and admittance control.